Electronic catalogue for press tools - Satya Budi. (2008)
This project implements a case study for an electronic catalogue, based on Die punches, produced by Misumi Corporation. The electronic catalogue consists of three representative parts in the category called Burring Die Units, Embossing Punches, and Engraving Punches. There are three main components for the electronic catalogue development: a database, structured query language (SQL), and user interface.